PHYTODIVERSITY AND SOIL STUDY OF SHIWALIK HILLS OF ILAM, NEPAL: AN ECOLOGICAL PERSPECTIVE - Nirola, Ramkrishna; Jha, Pramod Kumar (Ecoprint: An International Journal of Ecology, 2013)
The Siwalik range (locally known as Churia hills) in Nepal comprise a total area of 1,886,000 ha, equivalent to 13% of the country’s total area and consists of hills, steep land slopes, gorges, large spans of river and temporary streams. Study of different kinds of plants, soil and climate and the quantitative analysis of vegetation structure and composition as well as soil analysis at three Village Development Committees (VDCs) of Siwalik hills of Ilam was undertaken. A total number of 137 flowering plants and 8 pteridophytes are reported in the present study. Shorea robusta, Terminalia alata and Semecarpus anacardium are the most dominant species of the entire study area. The Siwalik range with late tertiary exposed rocks consists of fine grained sandstone with pockets of clay, shale, conglomerate and freshwater limestone. The vegetation is much more diverse and intact ecologically than expected from a distant observation. DOI: http://dx.doi.org/10.3126/eco.v18i0.9414 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: Uploaded date: 12/22/2013